The feasibility of liberalisation or deregulation of air transport in the GCC - Al-Suliaman, Saed (Cranfield University, 1992)
Many nations worldwide have been influenced by the experience of the USA in airline deregulation and have begun to consider the reform of their own governmental regulations. However, airline deregulation has both advantages and disadvantages for consumers, individual airlines, shareholders, the airline industry and governments. Western Europe has been under pressure to relax its regulations and introduce a liberalisation process. This pressure came partly from the outside as a result of the USA experience and the challenge from low cost Asian carriers. However, pressure also came from the inside from the European Commission and consumer organisations. In May 1981, the Gulf Cooperation Council (GCC) was established between Saudia Arabia, Qatar, U.A.E., Kuwait, Bahrain and Oman. One of the ways to achieve the GCC’s goal of confederation is through economic integration, which means the establishment of a Gulf Common Market. The main objective of this thesis is to research the feasibility of airline liberalisation in the GCC, taking into consideration the US experience and the European expectation in this particular field. To accomplish that objective, this thesis is divided into three parts. The first part analyses and studies the GCC air transport market, the development and impact of the US Airline Deregulation Act and the European liberalisation process. The second part develops a feasibility model for air transport liberalisation in the GCC. This model involves modelling demand for domestic GCC scheduled air services, fleet planning and aircraft selection, financial analysis and the possibility of a new GCC network. Finally, the third part sets out the conclusions from this theoretically based feasibility study of air transport liberalisation in the GCC, the main findings of the thesis and lessons that were learned from the USA and Europe. Its principal conclusion that liberalisation is both feasible and desirable is backed up with an outline of a possible first step that could be adopted for introducing an airline liberalisation process to the GCC market. This process starts by liberating intra-GCC services using aircraft of less than 70 seats capacity. On a practical level, the thesis also recommends that the Air Transport Section of the GCC Department of Transportation should co-ordinate changes to GCC institutions and infrastructure and should propose further changes to regulation as the liberalisation process moves ahead. It recommends that the Air Transport Section should use developments of this model to evaluate additional changes to the framework of regulation.